Spirits of just men mountaineers, liquor bosses, and lawmen in the moonshine capital of the world - Thompson, Charles Dillard, 1956- (University of Illinois Press, 2011)
"Following the end of Prohibition in 1933, demand for moonshine remained high due to taxes imposed on large liquor producers. Seeking to answer this demand were the distillers of Appalachia who, having established illegal networks of moonshine distribution under Prohibition, continued their activities and effectively skirted the federal liquor tax scheme. Spirits of Just Men chronicles the Great Moonshine Conspiracy Trial of 1935, held in Franklin County, Virginia, a place that many still refer to as the "Moonshine Capital of the World." While the trial itself made national news, Thompson uses the event as a stepping-off point to explore Blue Ridge Mountain culture, economy, and political engagement in the 1930 illustrating how participation in the moonshine trade was a rational and savvy choice for farmers and community members struggling to maintain their way of life amidst the pressures of the Great Depression and pull of the timber and coal-mining industries in Virginia. Through Thompson's prose, local characters come alive as he pays particular attention to the stories of a key witness for the defense, Miss Ora Harrison, an Episcopalian missionary to the region, and Elder Goode Hash, itinerant Primitive Baptist preacher and juror in a related murder trial. Thompson explores how local religious belief both clashed with and condoned the moonshine trade and how stills and the trade enabled a distinctive cultural formation in the region that goes far beyond the hillbilly stereotype alive today. Not only is his work based on extensive oral histories and local archival material, but Thompson himself is from the area and his grandparents were involved in not only the moonshine trade but the trial as well"--